2001
DOI: 10.1105/tpc.010069
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Abnormalities and Reduced Fruit Softening in Tomato Plants Expressing an Antisense Rab11 GTPase Gene

Abstract: A cDNA clone from tomato fruit encodes a protein with strong homology with the rab11/YPT3 class of small GTPases that is thought to be involved in the control of protein trafficking within cells. The gene, LeRab11a , showed a pattern consistent with a single copy in DNA gel blots. The corresponding mRNA was developmentally regulated during fruit ripening, and its expression was inhibited in several ripening mutants. Its reduced expression in the Never-ripe mutant indicates that it may be induced by ethylene in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
4

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(21 citation statements)
references
References 37 publications
1
16
0
4
Order By: Relevance
“…The complex metabolic changes that occur during both maturation and ripening, for example in the cell wall, requires also a tight control of the trafficking routes and it is not surprising that the levels of these proteins are maintained constant throughout the ripening process. Perturbation of the trafficking process has a great effect on the fruit phenotype: silencing of the Rab11 GTPase gene leads to reduced levels of pectinesterase and polygalacturonase in the fruit and delayed softening 68 , as well as an increased proportion of cellulose concomitant to a reduction in pectin 44 . SlRab11a may therefore be important for pectin trafficking during fruit development.…”
Section: Discussionmentioning
confidence: 99%
“…The complex metabolic changes that occur during both maturation and ripening, for example in the cell wall, requires also a tight control of the trafficking routes and it is not surprising that the levels of these proteins are maintained constant throughout the ripening process. Perturbation of the trafficking process has a great effect on the fruit phenotype: silencing of the Rab11 GTPase gene leads to reduced levels of pectinesterase and polygalacturonase in the fruit and delayed softening 68 , as well as an increased proportion of cellulose concomitant to a reduction in pectin 44 . SlRab11a may therefore be important for pectin trafficking during fruit development.…”
Section: Discussionmentioning
confidence: 99%
“…The protein profile of these EVs was distinct from that of whole sunflower extract and also contained a protein showing 68% identity with human Rab11a GTPase, a mammalian exosome protein identified in several proteomic studies (92) which promotes the docking and the fusion of MVBs with the plasma membrane (556, 684). Rab11 GTPases were also involved in secretion and recycling of cell wall components in tomato (685) and polarized pollen tube growth in tobacco (686). Here, coordinated Rab11 GTPase activity was required for essential membrane trafficking, protein secretion and cell wall modification during fruit ripening.…”
Section: Function Of Evs In Plantsmentioning
confidence: 99%
“…Transgenic tomato plants expressing antisense mRNA for LeRAB11a under the constitutive promoter produced fruits that changed color properly upon the ripening but remained firm for a long time (indicating the possibility for extended storage). The same authors also observed reduced activity of pectinesterase and polygalacturonase in the apoplast of these transgenic tomatoes [75]. Roles of RAB GTPases and other prenylated proteins in plant pathogen resistance have already been mentioned, and research focused on their function should not only bring new interesting discoveries in the near future, but also new biotechnology applications.…”
Section: Biotechnology Applications Of Stress Prenylation Researchmentioning
confidence: 88%